2016
DOI: 10.1038/ijo.2016.42
|View full text |Cite
|
Sign up to set email alerts
|

Increased body mass index is associated with specific regional alterations in brain structure

Abstract: Background:Although obesity is associated with structural changes in brain grey matter, findings have been inconsistent and the precise nature of these changes is unclear. Inconsistencies may partly be due to the use of different volumetric morphometry methods, and the inclusion of participants with comorbidities that exert independent effects on brain structure. The latter concern is particularly critical when sample sizes are modest. The purpose of the current study was to examine the relationship between co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
91
3
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(108 citation statements)
references
References 55 publications
12
91
3
2
Order By: Relevance
“…Increasing BMI at midlife was also associated with atrophy in right lingual gyrus, anterior cingulate, and the peri-calcarine sulcus. A recent cross-sectional study by Medic et al also found a negative association between anterior cingulate thickness and BMI, which they postulated might have relevance for reward evaluation and decision control in obesity [23].…”
Section: Discussionmentioning
confidence: 99%
“…Increasing BMI at midlife was also associated with atrophy in right lingual gyrus, anterior cingulate, and the peri-calcarine sulcus. A recent cross-sectional study by Medic et al also found a negative association between anterior cingulate thickness and BMI, which they postulated might have relevance for reward evaluation and decision control in obesity [23].…”
Section: Discussionmentioning
confidence: 99%
“…In the context of the obesity pandemic, these findings have spurred neuroimaging research into health-harming weight gain. Structurally, elevated BMI has been consistently related to reduced grey matter (GM) and white matter (WM) integrity in the adult and ageing brain (Kurth et al, 2013;Medic et al, 2019Medic et al, , 2016Pannacciulli et al, 2006;Ronan et al, 2016). However, whether adiposity impacts on the developing brain, particularly during critical periods of accelerated GM and WM changes, remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Elevated BMI (Ho et al, 2010;Raji et al, 2010) and obesity (Gunstad et al, 2009;Yokum et al, 2012) have been associated with reduced total GMV; however, body mass has been consistently unrelated to global mean CT. Local GMV reductions have been observed in the OFC and the anterior cingulate cortex with increasing BMI (Raji et al, 2010), and decreased posterior parietal and temporal volumes have been reported in overweight adults (Gunstad et al, 2009;Walther et al, 2009). Studies examining local CT alterations have primarily shown BMI-related thinning in the left inferior parietal cortex, the inferior temporal and insular cortex (Hassenstab et al, 2012;Veit et al, 2014), and the prefrontal cortex, including ventromedial (Medic et al, 2016), superior frontal and orbitofrontal (Marqués-Iturria et al, 2013) regions. Although the structural correlates of neurocognitive phenotypes in obesity remain poorly characterised, reduced thickness in the superior frontal gyrus has been related to poorer performance on an inhibitory control task and higher BMI (Lavagnino et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Our results are highly consistent with studies conducted in adults. Cortical thinning linked to BMI was also described in the left LOC (Medic et al, 2016), as well as in the left inferior parietal cortex, including LOC and fusiform areas, and the right precentral gyrus (Veit et al, 2014). Both studies carried out vertex-wise correlations with a wide range of BMI that included healthy and unhealthy values that are compatible with obesity.…”
Section: Associations Between Cortical Gray Matter and Bmimentioning
confidence: 99%